A Normalized Approach for Service Discovery - Sambasivam, G.; Ravisankar, V.; Vengattaraman, T.; Baskaran, R.; Dhavachelvan, P. (Procedia Computer Science, 2015)
In today’s world web services are the known perception to all the users who uses the internet. The Web Service process involves service discovery, selection and ranking. Discovery is the process of matchmaking of user query with advertisements in the repository. Our motivation is to develop a model for web service discovery with the combined approach of service selection and ranking. In this paper, we have proposed a technique for web service discovery process, combining the keyword search and semantic search and ranking the services. The implementation results show that the proposed model performs better for the web service discovery process.
Keywords: Web Service Discovery; QoS; Keyword; Semantic; Ranking